Mosquito Community in Primate Captivity (Tarsius sp.) and its Potential as Transmitters of Zoonotic Mosquito-Borne Diseases. (Indonesian Journal of Primatology, 2023)
By means of conservation, ectoparasites monitoring and surveillance especially mosquitoes in primate captivity become important. Mosquito is one of the ectoparasites which acts as a vector of various types of zoonotic diseases such as Dengue, Zika, Japanese encephalitis, Rift Valley fever, filariasis, and others. This study was aimed to determine the diversity of mosquito species, their fluctuations as well as the potential of mosquitoes as a Dengue virus (DENV) vector around the tarsier captivity in the animal conservation laboratory IPB Primate Research Center (IPB PRC). Mosquitoes were collected from February to April 2020 using light traps and sweep net every two hours from 06.00 pm to 06.00 am. Detection of the presence of Dengue virus (DENV) is carried out using Reverse Transcriptase Real-time Polymerase Chain Reaction (RT-qPCR) against Aedes albopictus and Armigeres subalbatus. The results showed that there were 4 species of mosquitoes caught around the tarsier captivity namely Aedes albopictus, Culex quinquefasciatus, Armigeres subalbatus, and Armigeres foliatus. The dominant mosquito species were Armigeres subalbatus (62.11%) and Aedes albopictus (41.61%). Detection of Dengue virus (DENV) serotypes 1, 2, 3, 4 in Aedes albopictus and Armigeres subalbatus gave negative results. The presence of mosquitoes that have the potential to carry zoonotic disease around the tarsier captivity in IPB PRC shows the potential for Mosquito-Borne Diseases to both tarsiers and human.